Predictive multiuser redirected walking using artificial potential fields - Hirt, Christian; Isaak, Noah; Holz, Christian; Kunz, Andreas (Frontiers in Virtual Reality, 2024)
3 Real walking is considered the best locomotion metaphor to explore virtual environments in 4 terms of user experience. Besides being intuitive for the user, walking captures the true feeling 5 of motion since visual and proprioceptive sensation harmonize well. The major disadvantage of 6 choosing walking over other locomotion metaphors consists of the physical constraints of the 7 available space, which is usually considerably smaller than the virtual environment. To address 8 this issue, Redirected Walking (RDW) introduces slight mismatches between a user’s visually 9 perceived path and their actual walking pattern, compelling them to subconsciously compensate 10 the inconsistency by adjusting their walking trajectory. As a result, users can be steered to 11 a certain degree and extensive virtual environments are effectively compressed into smaller 12 physical spaces. Among others, particularly predictive RDW still offers lots of potential to grow 13 since it unites a variety of algorithmic systems, whereas many approaches from literature depend 14 on drastic restrictions like single user constraints or architectural limitations to ensure real-time 15 performance. 16 In this paper, we present two novel predictive RDW systems, which allow multiple physically 17 co-located users to explore independent, unconstrained virtual environments. The systems rely 18 on two new implementations of prediction systems based on clothoidic trajectory generation 19 combined with a cost-based planning concept built on non-harmonic artificial potential fields 20 (APF), which inherently allow for non-convex and dynamic physical environments. Using the APF, 21 three additional RDW conditions popular in literature are implemented for comparison purposes. 22 The overall five RDW concepts are validated in an extensive user study with 150 participants, 23 conducted in 75 pairs. The results indicate that the novel predictive RDW systems outperform 24 the other three literature conditions except for particular sections of the virtual environment with 25 specific architectural traits.